HOW AI IS RESHAPING THE MODERN WORKPLACE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Across all industries, artificial intelligence (AI) is changing the modern workplace. This article looks at how AI is currently being used, which job categories are most affected, and what opportunities and challenges it presents. While automation may replace some repetitive tasks, AI can create new rules and enhance human abilities. AI has improved productivity and decision-making in certain industries, as demonstrated by real-world examples from the creative, customer service, and healthcare sectors. The article also highlights the importance of upskilling and the importance of human skills like emotional intelligence and critical thinking. This article gives an easy-to-read summary of AI's expanding impact and offers helpful tips for getting ready for an AI-driven future.